Plasma levels of interleukin-17, interleukin-23, and transforming growth factor-β in Sudanese patients with vitiligo: A case-control study - Ali Malik Osman; Maowia Mohamed Mukhtar; Khalid Hussein Bakheit; Hamdan Zaki Hamdan (Wolters Kluwer Medknow Publications, 2015)
Background: Vitiligo is the most common pigmentary skin disorder. It is a multifactorial polygenic disease with epidermal melanocyte destruction. The cytokines profile found in vitiliginous patients was not fully elucidated. Aims: We sought to assess the autoimmune nature of vitiligo by comparing plasma levels of interleukin (IL)-17, IL-23, and transforming growth factor beta (TGF-b) in adult Sudanese vitiligo patients with matched control individuals. Subjects and Methods: Case-control study was conducted in Khartoum Dermatologic Teaching Hospital, in the period between July and December 2013. The cases were 42 adult Sudanese vitiligo patients matched with 43 control individuals. The cytokines were measured in the plasma by the quantitative "sandwich" ELISA. Results: Patients showed a significant lower median (25-75 th inter-quartile) of TGF-β than control (0.042 [0.041-0.044] vs. 0.047 [0.042-0.049]; P ͳ 0.001). Both IL-17 and IL-23 showed no significant difference between cases and controls. IL-17 showed a significant inverse relationship when correlated with TGF-β (r = −0.24; P = 0.026) while showing direct relationship when correlated with age (r = 0.28; P = 0.009). Conclusion: The positive findings detected in this study coincide with the important immunoregulatory role of the TGF-β, and support the autoimmune nature of the disease.